Use of Percutaneous Ethanol Injection Therapy for Recurrent Secondary Hyperparathyroidism after Subtotal Parathyroidectomy - Walter G. Douthat; Gabriela Cardozo; Gabriela Garay; Santiago Orozco; Carlos Chiurchiu; Jorge de la Fuente; Javier de Arteaga; Pablo U. Massari (International Journal of Nephrology)
We evaluated the efficacy of percutaneous ethanol injection therapy (PEIT) as a therapeutic option for recurrence of secondary hyperparathyroidism after subtotal parathyroidectomy in ESRD patients. Six patients underwent PEIT. A mean of 1.3 ± 0.8 ethanol injections was performed. Nodular volume was 1.5 ± 1.7 cm3, and 2.8 ± 2.8 cm3 of ethanol was injected per patient. After ethanol injection PTH decreased significantly (1897 ± 754 to 549 ± 863 pg/mL (P<.01)). There was also a reduction in serum calcium, phosphorus and calcium-phosphorus product. A positive and significant correlation was found between nodular volume with ethanol injected and time from parathyroidectomy. Only one patient required hospitalization due to severe hypocalcaemia. In other two cases, local discomfort and temporary mild dysphonia were registered. PEIT is an effective treatment to control recurrences of secondary hyperparathyroidism postsubtotal parathyroidectomy.